Internet gaming disorder, attention deficit hyperactivity disorder and learning in adults: a systematic review - Zhou, Xiaodeng; Chen, Juntao; Yao, Jiahua; Chui, Derek Tinyol; Tang, Su-Kit (Frontiers in Psychiatry, 2026)
The comorbidity between attention deficit hyperactivity disorder (ADHD) and Internet gaming Disorder (IGD) has attracted much attention. The aim of this systematic review was to explore the specific association between ADHD and IGD/GD Adult learning group. Through the literature search of MEDLINE, PUBMED and CINAHL, a total of 14 relevant studies were included. The study found that ADHD symptoms (especially inattention and hyperactive impulsivity) were significantly associated with the incidence and severity of IGD/GD, suggesting that ADHD may be an important risk factor for IGD/GD. Individuals with comorbidity not only have higher mental health problems such as depression and anxiety, but also show lower self-control and higher emotionality. In addition, five factors have been mentioned as potentially mediating the association between adult ADHD symptoms and IGD/GD symptoms: mental health, gender difference, cultural context, gaming motivation and game type, and living habit. Furthermore, IGD/GD has a negative impact on academic performance in adults with ADHD. The results of this review contribute to a better understanding of the complex relationship between ADHD and IGD/GD adult learning group and provide new perspectives for clinical intervention and treatment.